Arguing the Just War in Islam: By John Kelsay (Cambridge: Harvard University Press, 2007. 263 pages.) (American Journal of Islam and Society, 2010)
Jihad has become a normal English word, a term to describe irrational violence,“holy war,” terrorism, and the generally rather nasty things that “badMuslims do.” John Kelsay, in this wonderfully succinct and accessible work,wants to argue that the real issue in discussing jihad is to make sense of legitimateviolence and how it may be deployed, and hence to locate the discoursewithin an existing discussion about just war theory. I am not generally sympatheticto the use of the comparable frame of just war theory because, as ajuridical and ethical concept it is rather limited, arising as it does out of a particularpolitico-theological context of medieval Catholicism. Having saidthat, any serious attempt to nuance jihad’s meaning in the contemporaryworld, to contextualize the discourse adequately and historically, and to posedifficult questions to those who appropriate it on the basis of a claim towardestablishing justice and acting in a just cause is welcome.Kelsay is interested in the contemporary debate about the nature ofpolitical ethics among Muslims. His book is not just an attempt to “whitewash”Muslims and their theologies from any culpability in the acts and ideologiesof the likes of al-Qaeda. While he does interrogate the theologicaland juridical reasoning of such terrorists, what he wants to show is not onlytheir distance from historically grounded narratives of jihad, but alsohow their reasoning may be shared. It is indeed foolish to argue that jihadiideology has nothing to do with reasoning about jihad as such; it is counterintuitiveand unhelpful. He also wants to indicate how the language of justwar is mutually supportive between the rhetoric of the “war on terror” andal-Qaeda’s war on the “Zionist-Crusaders” (which is, in theological terms,the subject of a forthcoming book by Alia Brahimi to be published by CambridgeUniversity Press) ...